Dog Fancying and its Social Problems: Analysis of Dog Keeping Problems and Social Dimension of its Peculiarity in Ibadan Metropolis, Nigeria - Akinyemi, Taiwo A. (ABUAD Journal of Social and Management Sciences, 2025)
Humans have coexisted with animals for centuries for the purposes of domestication, companionship, and ecological interactions. However, this bond is not without its challenges; it carries risks for humans that must be taken seriously and addressed appropriately. This study examined the various challenges peculiar to dog keeping in the Ibadan metropolis, Nigeria. The study adopted a quantitative approach to data collection, with 200 volunteers from the pool of dog enthusiasts across the headquarters of eleven (11) local governments, and made use of Robert K. Merton’s strands of functionalism for solidification. The findings show that there are certain social problems peculiar to dog keeping that could constitute a threat to humans. It concludes that measures should be in place for total compliance – on the part of dog owners – with all regulations such as obtaining all needed vaccines for dogs that will help to save lives, curbing the spread of diseases that may be contracted, and ultimately, promoting life on earth for both human and non-human beings.